Impact of justice-related dispositions on support for cyber vigilantism: The mediating effect of perceived severity of transgression - Tan, Wei Liang (Legal and criminological psychology, 2022)
The prevalence of cyber vigilantism during this COVID-19 pandemic is an imminent issue that warrants our attention. However, there is a dearth of research regarding cyber vigilantism, especially from a personality perspective. Therefore, the current study aims to address this gap by examining the impact of justice-related dispositions such as legal authoritarianism and observer sensitivity on support for cyber vigilantism. Additionally, perceived severity of transgression was examined as a potential mediator. A total of 647 Singaporean participants (Mage = 23.16 years, SDage = 4.97) completed an anonymous online survey. Mediation analysis revealed an indirect effect: Perceived severity of transgression served as a mediator in the path between justice-related dispositions (i.e. legal authoritarianism and observer sensitivity) and support for cyber vigilantism, whereas there was no significant direct effect of justice-related dispositions on support for cyber vigilantism. The overall model predicted support for cyber vigilantism modestly, accounting for approximately three per cent of the variance. Findings of this study have theoretical implications that may be beneficial for both academics and law enforcement.